The Impact of Lease Capitalisation on Financial Statements and Key Ratios: Evidence from Australia - Karen Wong; Mahesh Joshi (Australasian Accounting, Business and Finance Journal, 2015)
The IASB/FASB exposure draft ED 2013 on lease accounting, if introduced as a standard, will fundamentally change the way that leases are accounted for and reported in financial statements. This paper seeks to provide information on the proposed new lease accounting rules and to illustrate their impact on financial statements and financial ratios of leading Australian companies. The study follows the method of constructive capitalisation developed by Imhoff et al. (1991) to demonstrate the potential impact of the new rules on financial ratios and financial statements. The results show that financial statements will change significantly when all lease assets and liabilities are capitalised. The study finds that lease capitalisation will have a material impact on the reported numbers in the balance sheet and income statement and result in significant changes to return and leverage ratios. A comparison between positive and negative income subgroups also shows significant changes in the financial ratios of both these sub- groups. This is the first Australian study that serves to provide computations of the effects on financial reporting changes in lease accounting standard. The results have practical implications for corporate managers and accounting practitioners in planning and formulating strategies to lessen the impact of this important change in lease accounting.
Keywords: accounting for leases; economic consequences; ED2010/9 and ED 2013/6; financial statement analysis; lease capitalisation